Enhancing Heat Stress Resilience in Broiler Chickens Through the Use of Probiotics and Postbiotics: A Review - Rakngam, S.; Zhu, Y.; Okrathok, S.; Pukkung, C.; Khempaka, S. (Tropical Animal Science Journal, 2024)
The broiler industry is currently the most important and rapidly growing livestock sector worldwide. However, it faces critical environmental issues, especially heat stress (HS). HS adversely affects the bird’s physiological and behavioural status, welfare, and growth performance, leading to numerous economic losses. Nevertheless, a limited understanding remains of the deep physiological and cellular responses related to energy formation and gut health. Therefore, the purpose of this review is to gain a better understanding of how HS affects broilers and to explore the potential of probiotics and postbiotics in mitigating HS effects, with a primary focus on antioxidant capacity, heat shock proteins (HSPs), gut health, and growth performance in HS-exposed broilers. HS induces various physiological and cellular responses related to energy metabolism, antioxidant defense, gut health, and inflammation. Probiotics and postbiotics, whether in single or mixed strains (such as Saccharomyces cerevisiae, Bacillus subtilis, Lactobacillus acidophilus, L. plantarum, and Enterococcus faecalis, etc.), have been shown to increase antioxidant enzyme activity, down-regulate HSP70 mRNA expression, and improve gut health through the enhanced gut morphology, strengthened barrier integrity, reduced inflammation, and restored gut microbial balance. Consequently, these benefits can lead to the enhanced growth performance in heat-stressed broilers. This indicates that probiotics and postbiotics hold promise as alternative feed additives to antibiotics for alleviating the negative effects of HS in the future. However, probiotics, being living microorganisms, are more sensitive and require conditions for viability and colonization in the gastrointestinal tract. Therefore, for practical application, postbiotics may offer greater effectiveness due to their safety, longer shelf life, and ease of storage, handling, and transportation.